2022
DOI: 10.1111/jasp.12916
|View full text |Cite
|
Sign up to set email alerts
|

Neoliberal ideology and negative attitudes toward immigrants: Evidence from a survey and survey experiment in Japan

Abstract: Existing research has emphasized that neoliberalism triggers anti‐immigrant attitudes. At the national level, this has been attributed to two context‐dependent mechanisms: the existence of radical right‐wing political parties that combine pro‐market ideology with authoritarian social conservatism, and an ethnically and racially heterogeneous environment in which immigrants are over‐identified as welfare recipients. However, these associations may not be context‐dependent because the majority of people tends to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
0
2
0
1
Order By: Relevance
“…Some scholars link favorable or unfavorable immigration attitudes to specific attributes of immigrants, such as the suggestion that high-skilled immigrants are more favored compared to low-skilled immigrants (Hainmueller and Hiscox, 2010;Hainmueller and Hopkins, 2015;Malhotra, Margalit, and Mo, 2013). One major distinction among immigrants that has drawn some attention is that between documented and undocumented immigrants (Hainmueller and Hopkins, 2015;Iragashi, Nakai, and Ono, 2023;Merolla, Ramakrishnan, and Haynes, 2013;Ramakrishnan, Easterling, and Neblo, 2014;Wright, Levy, and Citrin, 2016). There is a consensus in this body of research that undocumented immigrants are less favorably evaluated than documented immigrants, and we also speculate here that there are strong differences in the determinants of evaluations of documented and undocumented immigrants.…”
Section: Previous Researchmentioning
confidence: 99%
“…Some scholars link favorable or unfavorable immigration attitudes to specific attributes of immigrants, such as the suggestion that high-skilled immigrants are more favored compared to low-skilled immigrants (Hainmueller and Hiscox, 2010;Hainmueller and Hopkins, 2015;Malhotra, Margalit, and Mo, 2013). One major distinction among immigrants that has drawn some attention is that between documented and undocumented immigrants (Hainmueller and Hopkins, 2015;Iragashi, Nakai, and Ono, 2023;Merolla, Ramakrishnan, and Haynes, 2013;Ramakrishnan, Easterling, and Neblo, 2014;Wright, Levy, and Citrin, 2016). There is a consensus in this body of research that undocumented immigrants are less favorably evaluated than documented immigrants, and we also speculate here that there are strong differences in the determinants of evaluations of documented and undocumented immigrants.…”
Section: Previous Researchmentioning
confidence: 99%
“…En ese sentido, Rita Edozie (2021: 99) sostiene que el neoliberalismo autoritario "pone en riesgo las democracias occidentales consolidadas", desestabilizando de manera evidente a las débiles e incipientes democracias del Sur global. En ese contexto, las políticas antiinmigrantes típicas del neoliberalismo autoritario no se han expresado sólo en Estados Unidos; también en otras zonas, donde estas personas son tratadas con desprecio, acceden a trabajos mal pagados e inseguros, y se les niega el acceso a la salud, lo que evidentemente vulnera sus derechos (Dutta, 2020;Igarashi y Ono, 2019).…”
Section: Formas Y Enfoques Del Neoliberalismo Autoritariounclassified
“…This neglect of post-arrival orientation can mean that Asian migrants' needs in disaster risk management are ignored. Igarashi and Ono (2019) suggested that in countries like Japan, neoliberal ideology can promote anti-immigrant attitudes. They argued that pro-market ideology, and in turn preference for labour with higher-level skills, are strongly promoted within a neoliberal framework.…”
Section: The Context Of Aotearoamentioning
confidence: 99%